Characterization of ecological risks from environmental releases of decamethylcyclopentasiloxane (D5). (24th July 2015) - Fairbrother, Anne; Burton, G. Allen; Klaine, Stephen J.; Powell, David E.; Staples, Charles A.; Mihaich, Ellen M.; Woodburn, Kent B.; Gobas, Frank A.P.C.
Abstract: Decamethylcyclopentasiloxane (D5) is used in personal care products and industrial applications. The authors summarize the risks to the environment from D5 based on multiple lines of evidence and conclude that it presents negligible risk. Laboratory and field studies show that D5 is not toxic to aquatic organisms or benthic invertebrates up to its solubility limit in water or porewater or its sorptive capacity in sediment. Comparison of lipid‐normalized internal concentrations with measured concentrations in benthos indicates that field‐collected organisms do not achieve toxic levels of D5 in their tissues, suggesting negligible risk. Exposure to D5 resulted in a slight reduction of root biomass in barley at test concentrations 2 orders of magnitude greater than measured D5 levels in biosolids‐amended soils and more than twice as high as the maximum calculated sorptive capacity of the soil. No effects were observed in soil invertebrates exposed to similar concentrations, indicating that D5 poses a de minimis risk to the terrestrial environment. High rates of metabolism and elimination of D5 compared with uptake rates from food results in biodilution in the food web rather than biomagnification, culminating in de minimis risk to higher trophic level organisms via the food chain. A fugacity approach substantiates all conclusions that were made on a concentration basis. Environ Toxicol Chem 2015;34:2715–2722. © 2015 SETAC